Ответы и объяснения

2012-03-10T17:10:36+04:00

Формулы:

cosa*cosb = 0.5(cos(a+b)+cos(a-b))  - произведение косинусов

cos2a = cos^2a - sin^2a = 2cos^2a - 1 - косинус двойного угла

 

1+cos2x + 2cosxcos3x = 1 + cos2x + 2*0.5(cos4x + cos(-2x)) = 1 + cos2x + cos4x + cos2x = cos4x + 2cos2x + 1 = 0 

Введем замену: y = 2x

cos2y + 2cosy + 1 = 0

2cos^2y - 1 + 2cosy + 1 = 0

2cosy(cosy+1) = 0

cosy = 0   или    cosy = -1

y = Pi/2 + Pi*k, k - целое число

или

y = Pi + 2Pi*k, k - целое число

Вернемся к замене

2х = Pi/2 + Pi*k     =>    x = Pi/4 + Pi/2 * k

или

2x = Pi + 2Pi*k       =>   x = Pi/2 + Pi*k